(3eNJGQGJ ef OjhGf ehSi Hf jMji HgQGf aj eOM GdEeGe TQa GdOjf jMji Hf TeS GdOjfs
(3ChdgG (B:s
(3HGJ SejQi hGdHQGjG gLhO HOQ JLdi ai djGdi GdSYhO s
(3BNQgG (B:s
(3MejJ ef GdCSQi hGdHDS hGdQOi hCHbGc QH GdYGdejf dfG PNQkG Je eG ESJMSf fbdg ef OjhGf ai ehdGfG GdEeGe TQa GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3cJHJ GdYfhGfGJ HGdMeQIs
(3GdeNJGQGJ ajgG cKjQ ef GdehTMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs